Comprehensive treatment of jaw bone defects caused by complications after COVID-19 (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
The problem of treatment of purulent-inflammatory diseases of the maxillofacial region is relevant both for dentists in clinics and maxillofacial surgeons in hospitals. As a result of not treating purulent inflammatory diseases on time, serious complications such as sepsis, mediastinitis, cavernous sinus thrombosis, and the development of atypical and severely developing phlegm on spreading in several cellular spaces at the same time were observed.: Research and development of orthopedic constructs to help patients restore jawbone function for comprehensive treatment of jawbone defects resulting from post-COVID-19 complications.